In situ binding: a modal analysis - Moortgat, Michael (Proceedings of the Amsterdam Colloquium, 1995)
In this paper we compare two multimodal deconstructions of the in situ bonder q(A, B, C), proposed in [9] for the scoping of generalized quantifiers. The wrapping analysis of [13] is shown to be of limited generality: it restricts the occurrence of generalized quantifier expressions to associative environments - environments where sensitivity for constituent structure is lacking. We propose an alternative deconstruction where the wrapping operation is independent of resource management assumptions about the structural context. The analysis is based on the general theory of structural control proposed in [8]: the interaction principles for the wrapping operation are fine-tuned in terms of unary modal control devices.